Efficacy and safety of azilsartan medoxomil in the treatment of hypertension: a systematic review and meta-analysis - Zhu, Ling; Wei, Guo-Cui; Xiao, Qing; Chen, Qian-Lan; Zhao, Qian; Li, Xiu-xia; Pan, Ling-ai; Xiong, Xuan (Frontiers in Cardiovascular Medicine, 2024)
Background Angiotensin II receptor blockers (ARBs) are utilized for the management of hypertension and diabetes. Previous meta-analyses suggested that azilsartan medoxomil (AZL-M) improved blood pressure (BP) reduction, but there were no safety findings or suggestions for patients with hypertension or diabetes. Methods We performed an efficacy and safety meta-analysis of randomized controlled trials (RCTs) evaluating AZL-M therapy for reducing BP in patients with hypertension. Patients with hypertension complicated by diabetes were analyzed. The relevant literature was searched in English and Chinese databases for RCTs involving AZL-M in hypertension. Efficacy variables included the change from baseline in the 24-h mean systolic/diastolic BP measured by ambulatory BP monitoring, the change from baseline in clinic systolic/diastolic BP, and responder rates. Safety variables included total adverse events (AEs), serious AEs, AEs leading to discontinuation, and AEs related to the study drug. The raw data from the included studies were utilized to calculate the odds ratio (OR) for dichotomous data and the mean difference (MD) for continuous data, accompanied by 95% confidence intervals (CIs). Statistical analysis was performed using R software. Results A total of 11 RCTs met the inclusion criteria, representing 7,608 patients, 5 of whom had diabetes. Pooled analysis suggested a reduction in BP among patients randomized to 40 mg of AZL-M vs. control therapy [24-h ambulatory blood pressure monitoring (ABPM) mean systolic blood pressure (SBP) (MD: −2.85 mmHg), clinic SBP (MD: −3.48 mmHg), and clinic diastolic blood pressure (DBP) (MD: −1.96 mmHg)] and for 80 mg of AZL-M vs. control therapy [24-h ABPM mean SBP (MD: −3.59 mmHg), 24-h ABPM mean DBP (MD: −2.62 mmHg), clinic SBP (MD: −4.42 mmHg), clinic DBP (MD: −3.09 mmHg), and responder rate (OR: 1.46)]. There was no difference in the reduction of risks, except for dizziness (OR: 1.56) in the 80-mg AZL-M group or urinary tract infection (OR: 1.82) in the 40-mg AZL-M group. Analysis of patients with diabetes revealed that AZL-M can provide superior management, while safety and tolerability were similar to those of control therapy. Conclusions AZL-M appears to reduce BP to a greater extent than dose-control therapy and does not increase the risk of adverse events in patients with hypertension and diabetes compared with placebo. Systematic Review Registration https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=464284, identifier PROSPERO CRD42023464284.